Magnetic nanoparticles applied in targeted therapy and magnetic resonance imaging: crucial preparation parameters, indispensable pre-treatments, updated research advancements and future perspectives. Issue 28 (29th June 2020) - Lin, Yaping; Zhang, Ke; Zhang, Ruihong; She, Zhending; Tan, Rongwei; Fan, Yubo; Li, Xiaoming
Abstract : We reviewed related updated research advancements of magnetic nanoparticles applied in targeted therapy and magnetic resonance imaging. Abstract : Magnetic nanoparticles (MNPs) have attracted much attention in cancer treatment as carriers for drug delivery and imaging contrast agents due to their distinctive performances based on their magnetic properties and nanoscale structure. In this review, we aim to comprehensively dissect how the applications of MNPs in targeted therapy and magnetic resonance imaging are achieved and their specificities by focusing on the following aspects: (1) several important preparation parameters (pH, temperature, ratio of the reactive substances, etc. ) that have crucial effects on the properties of MNPs, (2) indispensable treatments to improve the biocompatibility, stability, and targeting ability of MNPs and prolong their circulation time for biomedical applications, (3) the mechanism for MNPs to deliver and release medicine to the desired sites and be applied in magnetic hyperthermia as well as related updated research advancements, (4) comparatively promising research directions of MNPs in magnetic resonance imaging, and (5) perspectives in the further optimization of their preparations, pre-treatments and applications in cancer diagnosis and therapy.